2020 - IFAD-EU/CCAFS CSA Monitoring: Doyogena Climate-Smart landscape (Ethiopia) - Bonilla-Findji, Osana; Eitzinger, Anton; Recha, John W.M.; Ambaw, Gebermedihin; Nigussie, Abebe; Tesfaye, Abonesh (2021)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Dogoyena Climate Smart Village (Ethiopia) in December 2020.